Odpowiedzi

2010-02-25T16:42:07+01:00
6x-2y=20
2x+8y=5 / * (-3)

6x-2y=20
-6x-24y=-15 dodajemy stronami i x się skraca

-26y = 5/ : (-26)
y = -5,2 -> podstawiamy do pierwszego równania

6x-2y=20
6x-2 * (-5,2) =20
6x + 10,4 = 20
6x = 20-10,4
6x = 9,6 / :6
x = 1,6

x=1,6
y = -5,2
2010-02-25T16:42:34+01:00
6x-2y=20/*4
2x+8y=5

24x-8y=80
2x+8y=5

22x=75/:22
x=3,4

6*3,4-2y=20
20,4-2y=20
2y=0,4/:2
y=0,2

x=3,4
y=0,2

2010-02-25T17:03:10+01:00
6x-2y=20 |-6x
2x+8y=5

-2y=20-6x |:(-2)
2x+8y=5

y= -10+3x
2x+8y=5

y= -10+3x
2x+8(-10+3x)=5

y= -10+3x
2x-80+24x=5

y= -10+3x
-80+26x=5 |₊ 80

y= -10+3x
26x=85 | :26

y= -10+3x
x≈3

y= -10+3*3
x≈3

y= -10+9
x≈3

y= -1
x≈ 3